Towards an Engagement-Aware Attentive Artificial Listener for Multi-Party Interactions - Oertel, Catharine; Jonell, Patrik; Kontogiorgos, Dimosthenis; Mora, Kenneth Funes; Odobez, Jean-Marc; Gustafson, Joakim (Frontiers in Robotics and AI, 2021)
Listening to one another is essential to human-human interaction. In fact, we humans spend a substantial part of our day listening to other people, in private as well as in work settings. Attentive listening serves the function to gather information for oneself, but at the same time, it also signals to the speaker that he/she is being heard. To deduce whether our interlocutor is listening to us, we are relying on reading his/her nonverbal cues, very much like how we also use non-verbal cues to signal our attention. Such signalling becomes more complex when we move from dyadic to multi-party interactions. Understanding how humans use nonverbal cues in a multi-party listening context not only increases our understanding of human-human communication but also aids the development of successful human-robot interactions. This paper aims to bring together previous analyses of listener behaviour analyses in human-human multi-party interaction and provide novel insights into gaze patterns between the listeners in particular. We are investigating whether the gaze patterns and feedback behaviour, as observed in the human-human dialogue, are also beneficial for the perception of a robot in multi-party human-robot interaction. To answer this question, we are implementing an attentive listening system that generates multi-modal listening behaviour based on our human-human analysis. We are comparing our system to a baseline system that does not differentiate between different listener types in its behaviour generation. We are evaluating it in terms of the participant's perception of the robot, his behaviour as well as the perception of third-party observers.